Self-Regulation Versus Self-Discipline in Predicting Achievement: A Replication Study With Secondary Data - Michaelides, Michalis P.; Durkee, Patrick (Frontiers in Education, 2021)
Self-regulation is one of multiple non-cognitive measures that have been found to relate to academic achievement. Zimmerman and Kitsantas (2014) have distinguished self-regulation from the construct of self-discipline and provided evidence that only the former is predictive of high-school GPA, while controlling for the latter. In this brief report we present a pre-registered replication study of their finding using secondary data obtained from a published article by Jung, Zhou, and Lee (2017). Despite minor differences in the sample, the measures and the analysis approach, the replication supported the original claim that self-regulation was predictive of academic achievement for undergraduate students, while self-discipline was unrelated to the outcome. The positive association for the self-regulation variable with academic achievement was smaller, but in the same direction as in the original study.